Privilegios y malogros de la familia Camarão - Ronald Raminelli (Centre de Recherches sur les Mondes Américains, 2008)
For one century, the Camarão family (Potiguar Indians) attempted to approach the monarchy and the Church. To achieve this objective, they abandoned their nomadic lifestyle, polygamy, cannibalism and slowly began to behave more as Christians and noblemen in search of honor and royal privileges, mainly through military services to the Portuguese Crown. These changes can not be interpreted only as a mere acculturation process, but as a mean to strengthening their power and leadership. Their alliance with the Portuguese was essential to the maintenance of their control over other indigenous groups, to perpetuate the patent of governorship and to guarantee the transmission of immaterial assets, as that alliance not only provided the Camarão family weapons and fortifications, but also gave them honors and privileges. Furthermore, Christian marriages assured the transmission of inheritance from Indians leaders to their sons, which might also include the honors and privileges of the fathers.